Development Of Video Learning Based On The Indonesian Language Signing System (SIBI) Method For Class II Deaf Chill At SDN 2 Bengkala Academic Year 2022/2023 - Ni Kadek Intan Wahyuni; I Made Suarjana; Dewa Ayu Puteri Handayani (Journal of Psychology and Instruction, 2021)
This research is development research (research and development). The product developed is Learning Video Media Based on the SIBI Method for Deaf Children, Grade II. This study aims to (1) determine the design of learning video media based on the SIBI method for grade II deaf students; (2) determine the validity of learning video media based on the SIBI method for grade II deaf children; and (3) determine the response of deaf students to learning video media based on the SIBI method for grade II deaf children. The 4D (four-D) model is a method used in the process of developing learning videos based on the SIBI method. The data collection method used is a questionnaire, which is then filled out by the respondents. Data analysis methods and techniques used in this research are qualitative and quantitative descriptive statistical analysis. In this SIBI method-based learning video media obtained a validation score by learning media experts of 94.5% (very good), then the validity test score by learning material experts was 97.85% (very good), then the results of media assessment through practitioner/teacher responses were 93.5% (very practical), and through student responses, a score of 86% (good). It is concluded that this development research obtained results with very good and very practical qualification levels, so that the products produced are feasible to be applied and used in the learning process for deaf children in grade II SDN 2 Bengkala